Ocean-human relations in the Anthropocene: mapping trends in sustainability-related marine social sciences articles - Pelke, Nane; Simonn, Finn Christian (Frontiers in Marine Science, 2023)
Research about ocean-human relations has significantly increased in recent years. Compared to other disciplines in the oceanic realm, the marine social sciences, as an umbrella term for diverse disciplines and research streams dealing with ocean-human relations, however only recently gained more attention. In this light, the UN Ocean Decade stresses marine social science’s pivotal role in assessing future trajectories toward more sustainable ocean-human relations. Our study aims to identify research trends in sustainability-related marine social sciences. Therefore, we thoroughly analyzed the metadata of 1,215 peer-reviewed articles published between 1991 and 2023 and retrieved from the Web of Sciences (WoS) database by applying various bibliometric analysis methods. Our study provides insights into (1) the scientific production of sustainability-related marine social sciences and its evolution (2) the main topics and research streams of sustainability-related marine social sciences, and (3) how these topics developed over time. The findings demonstrate a significant increase in annual scientific production as time progressed, with some countries and institutions contributing more than others. We identified, discussed, and visualized six research streams: (1) Perceptions and benefits of marine conservation; (2) Fisheries, aquaculture, and food security; (3) Climate change and climate change responses; (4) Coastal landscape and land use change; (5) Coastal and marine management; and (6) Development and ocean-human health. Based on those discussions, our study points to four future avenues for research and discussions marine social sciences could potentially build on. These include (1) strengthening the capacity of sustainability-related marine social sciences; (2) enhancing cross-country studies and cooperation; (3) fostering dialogue between marine natural and social scientists; and (4) making (more) sense of sustainability-related marine social science’s epistemic features.